2018
DOI: 10.1093/ageing/afy072
|View full text |Cite
|
Sign up to set email alerts
|

Lower blood pressure during antihypertensive treatment is associated with higher all-cause mortality and accelerated cognitive decline in the oldest-old. Data from the Leiden 85-plus Study

Abstract: lower systolic blood pressure in the oldest-old taking antihypertensives was associated with higher mortality and faster decline in cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 28 publications
4
51
2
5
Order By: Relevance
“…Interestingly, in very old frail subjects, several recent observational studies have shown that low SBP levels (SBP <130 mm Hg) were associated with higher morbidity and mortality rates in those receiving BP-lowering drugs but not in those with spontaneously (nondrug-related) BP levels. [73][74][75][76] These observational findings may be because of reverse causality because having BP-lowering medication in old age probably reflects longer hypertension history with its consequences during life-course and, therefore, higher mortality risk than among people without medication. Another interpretation is that the medication-related decrease in BP in these very frail individuals could worsen -not improve -the prognosis.…”
Section: Bp and Reverse Causalitymentioning
confidence: 99%
“…Interestingly, in very old frail subjects, several recent observational studies have shown that low SBP levels (SBP <130 mm Hg) were associated with higher morbidity and mortality rates in those receiving BP-lowering drugs but not in those with spontaneously (nondrug-related) BP levels. [73][74][75][76] These observational findings may be because of reverse causality because having BP-lowering medication in old age probably reflects longer hypertension history with its consequences during life-course and, therefore, higher mortality risk than among people without medication. Another interpretation is that the medication-related decrease in BP in these very frail individuals could worsen -not improve -the prognosis.…”
Section: Bp and Reverse Causalitymentioning
confidence: 99%
“…23,24 Based on our earlier study, in which we followed an older cohort over a period of 5 years, we found no evidence that this decline would stop after 1 year or regress to the mean. 17 Our present study builds on a study by Mosello and Simoni 25 but is much larger (1,266 vs 172 participants) and was conducted in a different setting (primary care vs outpatient memory clinics). Mosello and Simoni 25 included only patients with dementia or mild cognitive impairment.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…15,16 In an earlier study, we reported in a population-based Dutch cohort of persons aged 85 years (n = 570) that low SBP was associated with increased all-cause mortality risk and cognitive decline but only in frail patients who were undergoing antihypertensive therapy. 17 In the present study, we set out to determine if low SBP and cognitive decline are similarly associated in a relatively younger cohort of persons aged ≥75 years in the primary care setting and with or without antihypertensive treatment. We also tested for an association between SBP and daily functioning and quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…As for the prevention of dementia by antihypertensive therapy, some studies suggest that the risk of dementia is increased by the potential hypotension in antihypertensive therapy due to the impaired vascular regulation mechanism in the elderly [36][37][38] . They did not clarify whether all MCI cases had late-onset hypertension and their follow-up time was too short.…”
Section: Mcip Cannot Benefit From Antihypertensive Therapymentioning
confidence: 99%